Antibody Titer Against Porphyromonas Gingivalis in Rats with Experimentally Induced Periodontitis - Parviz Torkzaban; Alireza Zamani; Rasoul Yousefimashouf; Javad Faradmal; Morad Hedayatipanah; Zahra Karimitabar (Islamic Dental Association of Iran, 2017)
Background and Aim: This study aimed to assess the antibody titer against Porphyromonas gingivalis (P. gingivalis) in rats with experimentally induced periodontitis. Materials and Methods: Thirty-three Surrey rats were randomly divided into three groups (n=11). Group 1 was vaccinated with formalin-killed whole cell (FKWC) P. gingivalis with incomplete Freund's adjuvant as vaccine carrier and orally inoculated with viable P. gingivalis (ATCC 33277). Group 2 was vaccinated with incomplete Freund's adjuvant and PG buffer and orally inoculated with viable P. gingivalis (positive control). Group 3 was vaccinated as group 2 without inoculation (negative control). Two weeks later, they were vaccinated with a booster dose. One week later, serum and saliva samples were obtained to assess antibody titer. Oral inoculation of bacteria was then done four times every 48 hours. Two weeks later, serum, saliva and subgingival plaque samples were obtained from the maxillary second molar area for assessment of P. gingivalis count in the subgingival plaque. Data were analyzed using Mann-Whitney U test and Wilcoxon signed-rank tests. Results: Serum and salivary antibody titers against P. gingivalis in group 1 one week af-ter booster dose and two weeks after oral inoculation of bacteria were significantly different from those in other groups (P<0.05). Groups 1 and 3 were not significantly different in terms of bacterial count in subgingival plaque (P=1.000) but the difference between groups 1 and 2 was significant (P<0.001). Conclusion: Vaccination with FKWC P. gingivalis increased serum IgG and salivary IgA and limited the colonization of P. gingivalis in subgingival plaque of rats.